Impact of Workplace Discrimination on Employee’s Wellbeing with Moderating Role of Situational Leadership - Pervaiz, Hina; Afridi, Fahad khan; Gill, Waqas Qayyum (Journal of Business & Tourism, 2024)
In this work, the impact of heuristic availability bias on financial decisions is attempted to be This study examines the relationship between workplace discrimination and employees’ well-being in the education sector of Peshawar, Khyber Pakhtunkhwa. It places special attention as situational leadership served as a moderator. Workplace discrimination is a major worldwide issue because of its severe and persistent effects on employees’ well-being. This study tries to identify the underlying reasons of discrimination and its detrimental effects on employees’ well-being with insightful findings. 265 respondents in the Peshawar education sector completed a structured questionnaire that was used to collect quantitative data. The results of this study have witnessed the great impact of discrimination on employees’ wellbeing. These results have important ramifications for human resource management practitioners and academics alike. Organizations can design focused initiatives to promote employee wellbeing by acknowledging the negative impacts of discrimination and the moderating role of situational leadership. In addition, the study emphasizes how critical it is to put HRM practices into practice that give priority to equity, diversity, and capable leadership to foster a positive work environment.